EU regional policy and Croatian regulatory framework - Zlatan Frohlich (European Regional Science Association (ERSA), 2010)
As a candidate country, which is ready to end negotiation process with EU in 2010, Croatian regional policy is closely tied into the EU accession strategy. A major objective will be to prepare for the introduction of EU cohesion policy and the Structural Funds. The pre-accession funds will contribute to that effort. This will require a significant effort on the part of the government to strengthen the institutional base for the management of the Funds - from the centre of government to regions across the country. The National Strategy for Regional Development will be a major part of that effort. The central logic of the Structural Funds (2007-2013) is that concentrating much of their resources on the least developed member states and regions, EU regional and cohesion policy can contribute to reducing disparities while raising the competitiveness of the EU as a whole. The outcome of this debate over the next years will have significant repercussions on the direction and management of new regional policy in Croatia. The national strategy sets the context for balanced regional development both at national and sub-national level as well as draws attention to development needs of the 'assisted areas' as well as counties highlighting their different development profiles. It brings together the main analytical parts: policy framework, institutional context and finally an assessment of the existing development interventions on county, NUTS 2 and assisted areas level. As Croatia actively prepares for accession to the EU, it is crucial that it is well prepared for the implementation of EU regional policy issues. It means that national documents and new adopted legislation should be in line with EU legal framework and procedures. In the paper will be analyzed complementarities between Croatian and EU legislation, with emphasize on Croatian regional development strategy issues.
Keywords: 330